The characterization of naturally occurring radionuclides in concrete incorporating fly ash as partial cement replacement - Mevlan Qafleshi; Misin Misini; Driton Kryeziu; Lulezime Aliko (Brazilian Journal of Radiation Sciences)
Kosovo thermal power plants (TPP) produce annually more than 1 million tons of fly ash as a byproduct of lignite combustion. The focus of this study was to characterize the activity concentration of natural radionuclides of hardened concrete specimens with Hyper Pure Germanium gamma-ray spectrometry (HPGe). Concrete mixtures with different content of fly ash as cement replacement were prepared.    Four concrete mixes with 15, 20, 25 and 30% fly ash replacing the respective content of cement were tested for activity concentration of 40K, 226Ra and 232Th, activity concentration index, indoor and outdoor specific and annual absorption dose rates. Two other reference mixes were normal concrete with cement. The obtained results were compared to reference concrete mixtures without fly ash.  The results of measurements in six concrete mixtures showed that the activity concentrations of 40K, 226Ra and 232Th were very low in all concrete specimens.